Pengaruh Orientasi Kewirausahaan dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT Gema Sembilan Sembilan di Tasikmalaya - Sri Wardatul Matoyah; Rizka Aula Assaf (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Competition in the business world requires companies to improve employee performance in order to achieve organizational goals. Entrepreneurial orientation and the work environment are factors that can influence employee performance in carrying out their duties. This study aims to analyze the influence of entrepreneurial orientation and the work environment on employee performance at PT Gema Sembilan Sembilan in Tasikmalaya. This study uses a quantitative method with descriptive and verifiable approaches. The research sample consisted of 98 respondents selected using simple random sampling. Data were collected through a questionnaire and analyzed using multiple linear regression. The results indicate that entrepreneurial orientation and work environment have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) of 63.2% indicates that employee performance can be explained by entrepreneurial orientation and the work environment, while 36.8% is influenced by other factors outside the research model. This study concludes that improving entrepreneurial orientation and the work environment plays a crucial role in enhancing employee performance at PT Gema Sembilan Sembilan in Tasikmalaya.